Social Support as a Form of Stress Coping Mechanism among Students Facing Social Problems in Islamic Boarding Universities - Jaziela Huwaida; Maya Tsurayya Alfadla; Siti Anne Barkah Nur Fauziah; Ilham Mulyadi; Puteri Azka Salsabila (Universitas Muhammadiyah Surakarta, 2025)
Islamic boarding colleges have many activities, both academic and non-academic. This causes some students to experience problems such as time management, relationships with friends, and other issues that lead to stress among students. Social support is one of the problem solvers used by these students. This research aims to understand the social problems commonly faced by student santris, the sources of social support available to student santris, and the forms of social support from parents, lecturers, and friends that can serve as coping mechanisms for the stress experienced by student santris. This research is a qualitative study with a phenomenological approach. The researcher aims to understand the phenomenon of what the research subjects experience related to perception behavior, motivation, actions, and experiences regarding forms of social support as a way to cope with stress in facing social problems at UNIDA Gontor. The results of this study indicate that the social problems commonly faced by student santris include issues such as discipline, friendship, and economic problems, while the social support for student santris is obtained from friends, parents, dormitory principals, academic and Islamic boarding University advisors, as well as the counseling team. The forms of social support provided to students experiencing stress include emotional support, recognition, and informational support, which can be ways to address the stress of students in facing social problems in the environment of Islamic boarding University higher education.